Factors associated with complications of parathyroidectomy in the elderly: A single-center experience (Annals of Medical Research, 2025)
Aim: The expanding older adult population has led to a corresponding increase in parathyroidectomy procedures among geriatric patients. Due to the prevalence of comorbidities and reduced physiological reserves, elderly patients may experience a greater incidence of postoperative complications. This study aims to evaluate the relationship between clinical parameters and complications associated with parathyroidectomy in individuals aged 65 years and above.Materials and Methods: This is an observational study included patients aged 65 years and older who underwent parathyroid surgery at a tertiary care center between January 2009 and February 2022. Demographic, clinical, surgical, and laboratory data were analyzed. Patients were divided into two groups according to the presence or absence of postoperative complications. A subgroup analysis was conducted for patients who developed permanent hypocalcemia. Statistical comparisons were made between groups. DEXA T scores were obtained from the lumbar spine and hip regions.Results: Elderly patients accounted for 5.9% (23/388) of all parathyroidectomy cases. The overall postoperative complication rate was 21.7%, and the rate of permanent hypocalcemia was 17.4%. Statistically significant differences were found between the patients with and without complications in terms of free T3, preoperative ALP, PTH, and postoperative calcium levels. Histopathological findings (adenoma vs. hyperplasia) and the number of excised adenomas were significantly associated with complications and permanent hypocalcemia. Mortality was significantly higher in the complication group (p=0.017). No cases of persistent hyperparathyroidism were observed during follow-up. A significant association was found between preoperative phosphorus levels and DEXA T-scores.Conclusion: Parathyroidectomy in elderly patients carries a notable risk of postoperative complications. Identifying high-risk patients based on clinical and biochemical parameters may help guide preoperative planning and postoperative monitoring.
Keywords: Elderly; Parathyroidectomy; Postoperative complications